2010
DOI: 10.1143/jjap.49.040212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wall Charge on Firing Voltage and Statistical Delay Time in Alternating-Current Plasma Display Panels

Abstract: The effects of wall charge on firing voltage, V f, and the statistical delay time of discharge, t s, in plasma display panels were investigated. V f, i.e., the ion-induced secondary electron emission, is independent of both the polarity and amount of wall charge. In contrast, t s, i.e., the exoelectron emission, strongly depends on the wall charge and is smaller for a high positive wall charge, revealing the coexistence of trapped electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…test panel. 19) The panel was sealed with a discharge gap of 100 mm and filled with the discharge gas of a Ne-Xe (10%) gas mixture at 60 kPa. The panel consisted of a pair of glass plates of the same structure facing each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…test panel. 19) The panel was sealed with a discharge gap of 100 mm and filled with the discharge gas of a Ne-Xe (10%) gas mixture at 60 kPa. The panel consisted of a pair of glass plates of the same structure facing each other.…”
Section: Methodsmentioning
confidence: 99%
“…The authors have been involved in the study of the effects of charging on the electron emission from insulator film surfaces. [13][14][15][16][17][18][19] In the previous study, we investigated the effects of the amount and polarity of wall charge on t s and found that a positive wall charge on the MgO surface of the cathode side is advantageous in improving the response of the discharge. 19) In this study, we investigated the effects of wall charge on the property of exoelectron emission in AC-PDPs, in particular, the accumulation and decay of exoelectron sources, by measuring the discharge characteristics, i.e., the statistical delay time, t s , using a specially designed test panel.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure. It has been reported that γ is closely related to defect states 16 and γ increases as the number of surface defect states in MgO increases.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that exoelectron emission from electron traps is much stronger, if there was a positive wall charge deposited in the previous cycle [1]. We therefore use Cathode Luminescence to simulate the joint presence of both free electrons and holes inside the crystal-type of protective layer.…”
Section: Introductionmentioning
confidence: 99%